On Resisting "Awayness" and Being a Good Insider: Early Career Scholars Revisit Coladarci's Swan Song a Decade Later - Catharine Biddle; Daniela Hall Sutherland; Erin McHenry-Sorber (Journal of Research in Rural Education, 2019)
This theoretical essay critically examines the impact of Coladarci's 2007 article, "Improving the Yield of Rural Education Research: An Editor's Swan Song," which he composed at the conclusion of his tenure as editor of the Journal of Research in Rural Education. Using boundary theory and "awayness" as a metaphor for understanding community in social science research, we use citation analysis to review the ways in which Coladarci's work has been taken up by the field, illustrating the ways in which this piece serves to socialize new researchers to rural education research. We then take up Coladarci's invitation to further discuss what might define a contribution to the field of rural education scholarship and propose several additional considerations, including analyses of how power manifests across space and the criticality of a topic to rural schools and communities.